(untitled) (Journal of International Studies, 2022)
This article talked about the position of academic researchers of the both neighbour regarding Mongolia’s «Third Neighbor» policy. Mongolia’s foreign policy analysis in south neighbour underway at the Academy of Social Sciences under the State Council of China, Global Times, the central daily newspaper of the CPC in chinese and english languages, School of International Studies, Beijing People’s University, Beijing Foreign Studies University. It should be emphasized that the Institute of Russian and Mongolian Studies of the Academy of Social Sciences, Inner Mongolia, the Department of Mongolian Studies of the Inner Mongolia University, the Inner Mongolian University of Education, and the Institute of Near Neighbour Studies of the Shanghai East China Normal University are concentrated. Regarding Russia, it is mainly focused on the Institute of Oriental Studies, the Institute of Far Eastern Studies, Russian Academy of Sciences, the Moscow State University, the Diplomatic Academy, MFA, the Russian International Affairs Council, St. Petersburg State University, Irkutsk State University, and Ulan-Udе University, ect., China’s researchers has a tendency in “advise” and some times “educate” to Mongolia on the importance of developing cooperation with its “real neighbour”. For Example, Mongolia’s geopolitical position shows that it should cooperate smartly with China and Russia. The researchers of Russia wrote that Mongolia’s “Third Neighbour” policy is utopian, and it is observed that the principle is “stuck” in its principles. Recently, the deepening of the geopolitical conflict between the two neighbour and the “third neighbour” is a matter of concern, and the criticism of the neighbouring countries is expected to transation from the level of Track 1 to the level of Track 1.5. Finally, The New paradigms of Mongolia’s foreign policy has priority to vital national interests, openness, peaceful, multi-pillars, multi-dimensional, non-Aligned, independently, priority to democratic values and pragmatism. It should be emphasized that it is not a policy directed against the two neighbors, but only peacetime geopolitics. Монгол Улсын «Гуравдагч хөрш»-ийн бодлого: Хоёр хөршийн судлаачдын дүн шинжилгээ Хураангуй: Монгол Улсын «гуравдагч хөрш»-ийн бодлогын тухайд хоёр хөршийн судлаачид ямар байр суурь, хандлагатай байна гэдэг анхаарал татсан нэн чухаг асуудал мөн. Өмнөд, Умард хөршүүд албан ёсны түвшинд дурдсан асуудалд тааламжгүй эсвэл бүр сөрөг байр суурь албан ёсоор илэрхийлж байгаагүй ч, олон улсын харилцаа, геополитик, стратеги судлаачид олон нийтийн хэвлэл, мэдээллийн хэрэгслүүд үзэл бодол, байр сууриа чөлөөтэй илэрхийлж ирсэн байна.